2016
DOI: 10.1038/srep38473
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Study of Light-assisted Polymerization by Multimechanism Action

Abstract: A novel bicomponent alkyd system was designed to decrease the usage of Cobalt-based drier due to its latent carcinogensis. The system was polymerized using a Cobalt-salt complex as an air-sensitive drier and an isopropylthioxanthone photoinitiator as a light-sensitive accelerator, as well as using irradiation in the form of visible light. The combined influence of the two additives on autoxidation was analyzed using real-time infrared spectroscopy. The results show that isopropylthioxanthone can increase the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thioxanthone is an historical photoinitiator of polymerization strongly absorbing in the near-UV/visible range and in this family, 2-isopropylthioxanthone (ITX) is one of the most relevant examples. [66,191,284] Due to its remarkable efficiency, this promising scaffold was logically examined for the design of various polymeric or macromolecular photoinitiators [280,[285][286][287][288][289][290][291][292], one-component photoinitiators [71,281,293,294] or multi-component photoinitiating systems. [65,[295][296][297] In 2020, the first example of phenothiazine/thioxanthone combination i.e.…”
Section: Thioxanthone Derivativesmentioning
confidence: 99%
“…Thioxanthone is an historical photoinitiator of polymerization strongly absorbing in the near-UV/visible range and in this family, 2-isopropylthioxanthone (ITX) is one of the most relevant examples. [66,191,284] Due to its remarkable efficiency, this promising scaffold was logically examined for the design of various polymeric or macromolecular photoinitiators [280,[285][286][287][288][289][290][291][292], one-component photoinitiators [71,281,293,294] or multi-component photoinitiating systems. [65,[295][296][297] In 2020, the first example of phenothiazine/thioxanthone combination i.e.…”
Section: Thioxanthone Derivativesmentioning
confidence: 99%
“…Any primary free radicals formed that manage to diffuse out of the solvent cage can add to the first monomer and so can propagate in free-radical polymerization, especially in use of multifunctional monomers within a dense network. Recombination of two radicles, disproportionation through proton abstraction, initiates the termination reaction that results in formation of a saturated and an unsaturated end, transferring the radicle to another molecule (Moad et al 2006;Zhou et al 2016).…”
Section: Photoinitiation and Photopolymerizationmentioning
confidence: 99%
“…During this irradiation process, a large amount of energy is absorbed as PI is converted into radicles. Decomposition of PI is dependent on light intensity and slightly less dependent on surrounding temperature(Zhou et al 2016). The radicals formed are classified as two distinct categories of photoinitiator molecules, Type I and Type II.…”
mentioning
confidence: 99%
“…Because paint is stored in closed cans, this provides a dark environment during storage, and we, therefore, considered light activation an interesting latency strategy to investigate. Previous work had already shown that the addition of photoinitiators and/or photosensitizers , such as bis­(2,6-difluoro-3-(1-hydropyrrol-1-yl)­phenyl)­titanocene ([(Cp) 2 Ti­(Ar F ) 2 ]), phenylbis­(2,4,6-trimethylbenzoyl)­phosphine oxide (BAPO), 1,2-diphenylethane-1,2-dione (benzil), 2-isopropylthioxanthone (ITX), rose bengal, and methylene blue (see Scheme for structures) can fasten the curing, but these approaches still required the use of either cobalt-based driers or the iron/bispidon complex, for which no suitable antiskinning method has been developed (addition of 2-butanone oxime does not work well). To the best of our knowledge, no systems have been reported that use light activation of the catalyst as a source of latency.…”
Section: Introductionmentioning
confidence: 99%